Dynamic cytological and transcriptomic analyses provide novel insights into the mechanisms of sex determination in Castanea henryi - Wu, Guolong; Tian, Xiaoming; Qiu, Qi; Zhang, Yue; Fan, Xiaoming; Yuan, Deyi (Frontiers in Plant Science, 2023)
Castanea henryi is a monoecious woody food tree species whose yield and industrialization potential are limited by its low female-to-male flower ratio. Here, the male flowers on the male inflorescence of C. henryi were converted to female flowers by triple applications of exogenous cytokinin (CK) (N-(2-chloro-4-pyridyl)-N’-phenylurea, CPPU). To study the role of exogenous CK in flower sex determination, cytological and transcriptomic analyses were performed on samples from the five stages after CK treatment. Cytological analysis showed that stage 3 (nine days after the last CK treatment) was the critical stage in the differential development of the pistil primordium and stamen primordium. On this basis, one key module and two modules with significant positive correlations with stage 3 were identified by weighted gene co-expression network analysis (WGCNA), combined with transcriptome data. The CK and GA biosynthesis- and signaling-related genes, three transcription factor (TF) families, and 11 floral organ identity genes were identified in the related modules. In particular, the TFs WRKY47, ERF021, and MYB4, and floral organ identity genes AGL11/15, DEF, and SEP1 with large differences are considered to be critical regulators of sex determination in C. henryi. Based on these results, a genetic regulatory network for exogenous CK in the sex determination of flowers in C. henryi is proposed. This study contributes to the understanding of the role of CK in the sex regulation of flowers and provides new insights into the regulatory network of sex determination in C. henryi.